The method of edge anxiety-depressive disorder correction in patients with diabetes mellitus - Kozhanova, A.; Chukhraeva, E.; Chuprikova, M.; Vladimirov, A.; Zukow, W.; Unichenko, A. (Journal of Education, Health and Sport, 2015)
Kozhanova A., Chukhraeva E., Chuprikova M., Vladimirov A., Zukow W., Unichenko A. The method of edge anxiety-depressive disorder correction in patients with diabetes mellitus. Journal of Education, Health and Sport. 2015;5(11):126-129. ISSN 2391-8306. DOIhttp://dx.doi.org/10.5281/zenodo.33596 http://ojs.ukw.edu.pl/index.php/johs/article/view/2015%3B5%2811%29%3A126-129 https://pbn.nauka.gov.pl/works/668011 Formerly Journal of Health Sciences. ISSN 1429-9623 / 2300-665X. Archives 2011–2014http://journal.rsw.edu.pl/index.php/JHS/issue/archive Deklaracja. Specyfika i zawartość merytoryczna czasopisma nie ulega zmianie. Zgodnie z informacją MNiSW z dnia 2 czerwca 2014 r., że w roku 2014 nie będzie przeprowadzana ocena czasopism naukowych; czasopismo o zmienionym tytule otrzymuje tyle samo punktów co na wykazie czasopism naukowych z dnia 31 grudnia 2014 r. The journal has had 5 points in Ministry of Science and Higher Education of Poland parametric evaluation. Part B item 1089. (31.12.2014). © The Author (s) 2015; This article is published with open access at Licensee Open Journal Systems of Kazimierz Wielki University in Bydgoszcz, Poland and Radom University in Radom, Poland Open Access. This article is distributed under the terms of the Creative Commons Attribution Noncommercial License which permits any noncommercial use, distribution, and reproduction in any medium, provided the original author(s) and source are credited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/3.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/3.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. The authors declare that there is no conflict of interests regarding the publication of this paper. Received: 05.09.2015. Revised 05.10.2015. Accepted: 30.10.2015. UDC 616.711: 615.846 + 615.837.3 THE METHOD OF EDGE ANXIETY-DEPRESSIVE DISORDER CORRECTION IN PATIENTS WITH DIABETES MELLITUS Kozhanova A.1, Chukhraeva E.2, Chuprikova M.3, Vladimirov A.3, Zukow W.4, Unichenko A.3 1. The branch of Almaty State Institute of Postgraduate Medical in Astana, Kazakhstan 2. National Medical Academy of Postgraduate Education. P.L. Shupyk, Kiev, Ukraine 3. Scientific and Methodological Center "Medintech", Kiev, Ukraine 4. Kazimierz Wielki University, Bydgoszcz, Poland Abstract The article presents the results of research on the effectiveness of the method developed by the authors for correcting the anxiety and depressive edge disorders in patients with type 2 diabetes through the use of magnetic-therapy. Tags: anxiety-depressive disorder, hidden depression, diabetes, medical rehabilitation, singlet-oxygen therapy.